The Census of Distribution - Cherington, Paul T. (The Review of Economics and Statistics, 1929)
T HE Census of Distribution taken in eleven cities a little over a year ago was of the nature of a practice effort for the Census of Distribution to cover the entire country, which it is hoped may be a part of the regular Decennial Federal Census of 1930.1 This preliminary census, therefore, has three sources of interest to the statistician: first, as an indication of what may be expected from this expansion of census efforts into a new field; second, as a means for classification of prevailing ideas about what such a census might cover and how; and third, as a source for a new group of data concerning distribution activities.